Using "make a match" methods for improving knowledge and preventive attitudes toward flour albus among adolescent - Nasution, Nur Arfah; Harahap, Nur Hamima; Dongoran, Rini Fitriani (Jurnal Prima Medika Sains, 2024)
Reproductive health issues remain prevalent among adolescents due to limited access to information. Fluor albus is a common concern among women. Global surveys indicate that approximately 75% of women experience at least one episode of abnormal vaginal discharge during their lifetime. Promotive and preventive interventions, including targeted health education, are crucial to improve adolescents' knowledge and attitudes regarding reproductive health and hygiene. This study investigated the effectiveness of the "Make a Match" educational method in enhancing knowledge and attitudes about leukorrhea prevention among adolescent girls. This quasi-experimental pre-posttest control group study examined the impact of the "Make a Match" method. The study population comprised female adolescents in Sitinjak Sub-district, South Tapanuli Regency. A total sample of 30 participants was recruited using total sampling. Data were collected using questionnaires, posters, and leaflets. Data analysis involved paired t-tests and Wilcoxon signed-rank tests. The results of the Wilcoxon tests revealed statistically significant differences in knowledge and attitude scores before and after the intervention (p < 0.001 for both variables). These findings demonstrate a significant improvement in both knowledge and attitudes related to leukorrhea prevention following the "Make a Match" health education intervention (p < 0.05). In conclusion, this study provides evidence that the "Make a Match" health education method effectively enhances knowledge and attitudes regarding leukorrhea prevention among adolescent girls. These findings underscore the need for enhanced community-based health education programs, particularly for adolescents, focusing on reproductive health.